Entuziasmul, intuția și empatia, forțe luptătoare în războiul nevăzut - Nemeș, Dan (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The strength of enthusiasm, the clarity of intuition and the power of empathy are the pillars of resistance in this unseen war. Enthusiasm in action leads to the strengthening of hope, the clarity of intuition enhances the faith, and the capacity for empathy forms the basis of our agape love for our fellow human beings. Let us remember that hope, faith and love are the main Christian virtues, indestructible and unconquerable. Consequently, all that strengthens them in manifestation (including enthusiasm, intuition and empathy, as personality traits) are beneficial weapons in every Christian’s unseen warfare with temptations, with sins and with the bearer of these manifestations of darkness, the wicked, cunning and relentless enemy. This battle is waged within the human soul and is waged throughout man’s life on this earth. On the outcome of this unseen warfare depends the salvation of every soul and the establishment of its eternal abode.